Value added taxation : the experience of the United Kingdom - Prest, A. R. (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1980)
This paper compares the value added tax (VAT) with other forms of taxation, particularly payroll taxes. He describes the structure of the tax in the United Kingdom, as it was when introduced in 1973 and as it has been changed. He appraises the theoretical attributes of VAT, its economic consequences, and its public acceptability.
Includes bibliographical references: p. 51-52.
asm 23/01/2019
Loans
Keywords: Value-added tax; American Enterprise Institute Studies in Tax policy